Total abdominal debranching hybrid thoracoabdominal aortic aneurysm repair versus chimneys and snorkelsCentral Message - Akiko Tanaka, MD, PhD; Gustavo S. Oderich, MD; Anthony L. Estrera, MD (JTCVS Techniques)
Open thoracoabdominal aortic aneurysm (TAAA) repair remains a surgical challenge. Hybrid and total endovascular repair have emerged as alternatives in treating TAAA. Total endovascular TAAA repair may be best performed with branched/fenestrated stent grafts. However, these technologies are not yet widely available. Thus, currently total endovascular TAAA repair using the chimney/snorkel techniques is considered a viable option in many centers.In this article, we briefly review 2 readily available techniques with off-the-shelf devices, hybrid procedure using total abdominal debranching, and total endovascular repair using chimney/snorkel procedures. The hybrid TAAA repair avoids thoracotomy but requires laparotomy and carries high morbidity and mortality (eg, operative mortality, 4%-26% and renal failure, 4%-26%), comparable to traditional open repair. The staged hybrid approach has been proposed to minimize the invasiveness of the procedure, whereas the associated risk of interval aortic deaths is not negligible. Total endovascular repair reduces the morbidity and mortality after TAAA repair (eg, operative mortality, 3%-20% and renal failure, 0%-20%). However, it is technically demanding and the risks of future reinterventions—and need for repetitive surveillance—is inevitable (eg, immediate type I endoleak, 7%-16% and 1-year branch patency, 93%-98%). Currently, there are not enough data to determine which less-invasive option for open repair in patients with TAAA is superior. These alternatives should complement each other and be applied to carefully selected populations as a part of the overall toolbox in treating TAAA.